Traditional Ethnozoological Practices of Galliformes by Indigenous Inhabitants in Koraput District of Odisha, India - Sabat, Bhawani; Kanwar, Ankeet; Holeyachi, Basavaraj S.; Kalle, Riddhika; Joshi, Kamal Kant; Singh, Ashutosh (Ethnobiology Letters, 2025)
Hunting has been a traditional human practice for centuries to exploit faunal resources for beneficial needs. Wild Galliformes are particularly hunted for bushmeat, ornaments, religious rituals, spiritual practices, and medicine. This study documents the traditional ethnozoological knowledge and practices of Galliformes utilized by the Indigenous inhabitants of Koraput district, Odisha, India. Information was collected using the Participatory Rural Appraisal (PRA) method through semi-structured interviews. We recorded eight Galliformes species utilized in 23 distinct ways. Six body parts (meat, skull, egg, feather, feet bone, and body oil) were used to treat 15 human ailments. Results indicated that oral application (52.1%) was the most effective mode of treatment, followed by topical application (47.8%). Among the reported species, feathers of Gallus gallus and Gallus gallus domesticus were most commonly used for treating ear-related complaints (Fidelity Level [FL] = 100%), while feathers of Pavo cristatus were least utilized, associated with predicting the birth of male children (FL = 6.7%). This study provides the first documentation of the ethnomedicinal use of three quail species (Coturnix coturnix, Perdicula erythrorhyncha, and Perdicula asiatica) in Odisha. This study also highlights three hunting techniques along with the cultural importance of the Galliformes and is the first quantitative ethnozoological analysis of Galliformes in the Koraput district, using FL percentage scores. Findings of this study emphasize the significance of Galliformes, linked with traditional ethnomedicine, hunting, and socio-cultural systems.